Burdened and fatigued: the hidden costs of supporting undocumented students in postsecondary contexts - Vega, Blanca Elizabeth (Frontiers in Public Health, 2025)
Sociopolitical and institutional barriers significantly influence the mental health and overall well-being of undocumented and Deferred Action for Childhood Arrivals (DACA) students in US higher education. Concurrently, higher education and student affairs (HESA) professionals who serve these students face their own psychological and professional challenges as they navigate restrictive policies and bureaucratic uncertainty. This brief research report extends the Immigration Battle Fatigue (IBF) framework by integrating principles from administrative burden theory to examine the interconnected experiences of undocumented students and the professionals who support them. Drawing on qualitative data from a Spencer Foundation–funded study of HESA professionals’ work with undocumented students, the analysis focuses on the psychological costs of immigration-related administrative burdens across four ecological levels: policy, institutional, interpersonal, and individual. Findings indicate that these psychological costs contribute to cumulative trauma, disengagement, and professional fatigue. The report concludes with implications for institutional practice, professional development, and policy reform to mitigate harm and promote systemic well-being.